2010
DOI: 10.1159/000285504
|View full text |Cite
|
Sign up to set email alerts
|

Level of Intended Sedation

Abstract: Sedation and analgesia is the standard of care during diagnostic and therapeutic endoscopic gastrointestinal procedures in most areas of the world. Unsedated endoscopy is feasible in selected patients, but requires commitment on the part of both the patient and the provider. The American Society of Anesthesiologists has defined four stages of sedation, ranging from minimal to moderate, deep and general anesthesia. The level of sedation as well as the choice of sedative is based on the type of procedure, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…According to the Standards of Practice Committee of the American Society for Gastrointestinal Endoscopy (ASGE), “sedation may be defined as a drug-induced depression in the level of consciousness” 17 . Sedation and analgesia for GIE aim to relieve the patient’s anxiety, fear and pain, minimize discomfort, improve the outcome of the examination, and diminish the patient’s recollection of the event 16 17 22 23 24 25 26 . Although their use improves tolerance and acceptance of the examination, they increase the cost and are responsible for about 50 % of all GIE complications 20 22 27 28 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the Standards of Practice Committee of the American Society for Gastrointestinal Endoscopy (ASGE), “sedation may be defined as a drug-induced depression in the level of consciousness” 17 . Sedation and analgesia for GIE aim to relieve the patient’s anxiety, fear and pain, minimize discomfort, improve the outcome of the examination, and diminish the patient’s recollection of the event 16 17 22 23 24 25 26 . Although their use improves tolerance and acceptance of the examination, they increase the cost and are responsible for about 50 % of all GIE complications 20 22 27 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Deciding on whether to use moderate, deep sedation or general anesthesia depends on patient characteristics, procedure demands and existence of the required structural conditions [9,10] . Common practice is the performance of ERCP under conscious sedation so most of the studies are targeted to a moderate level of sedation.…”
Section: Deciding On the Level Of Sedationmentioning
confidence: 99%
“…Endoscopists and nursing stuff should be board certified in intensive medicine and resuscitation to ensure the patient’s comfort and safety. The providers should be properly trained in the administration of endoscopic sedation and should possess the skills necessary for the diagnosis and management of sedation-related adverse events, including rescue from a level of sedation deeper than that intended [ 57 , 58 ]. Greek studies have shown that propofol-based sedation has not largely been adopted by the endoscopic community, mainly because of medicolegal reasons and inadequate training [ 31 , 59 ].…”
Section: Introductionmentioning
confidence: 99%